From Silence to Speaking Up: Students' Affective and Cognitive Exploration of Interactive Digital Media in EFL Speaking Learning - Anggraini Sifaus Syauqiah; Mohammad Sofyan Adi Pranata (JURNAL ILMIAH GEMA PERENCANA, 2026)
This study aims to explore students’ affective and cognitive experiences in learning EFL speaking through interactive digital media, focusing on their transformation from passive and anxious learners to more confident speakers. Using a qualitative method with a descriptive phenomenological design, the research was conducted in class XI IPA 2 at SMAN Paiton. Participants were selected purposively. Data were collected through semi-structured interviews, classroom observations, and documentation, and analyzed thematically. The findings indicate significant affective and cognitive changes. Students experienced reduced anxiety, increased motivation, and stronger self-confidence. Interactive digital media created a safer and more engaging learning environment. Cognitively, students showed improved comprehension, pronunciation awareness, idea development, fluency, and autonomous learning strategies. The study concludes that interactive digital media functions as both affective and cognitive mediation in EFL speaking instruction. It is recommended that teachers integrate digital tools systematically to support students’ emotional readiness, active participation, and long-term communicative competence.